Comprehensive analysis and experiment validation of five cuproptosis-related genes in prognosis, immune infiltration and metabolic characterization of pancreatic cancer. - Qianxi Deng; Kun Yang; Qiaoling Liao; Xueli Tang; Honglin Quan; Guojun Yuan; Xia Hu; Zheng Jiang; Linju Wu (PLoS ONE)
Background Cuproposis is a new-found mechanism of cell death, and the role of cuproposis-related genes (CRGs) in pancreatic cancer prognosis remains uncertain. Methods DECRGs were identified from TCGA and GTEx databases. Five OS-associated hub genes were screened using Cox regression and LASSO analyses. A prognostic model was constructed and validated by survival analysis. GSEA, gene mutation, small-molecule drugs, immune-infiltrating and TF/miRNA/mRNA network were investigated to determine the underlying mechanism of 5-CRGs. In addition, RT-qPCR, and WB were applied to validate the expression of 5-CRGs. CCK8, colony formation and transwell assays were used to prove the function of LIPT1 in PC. Results PDP1, DLAT, DBT, LIAS, and LIPT1 were screened as hub genes. 5-CRGs prognostic model established the low-risk population has a longer OS. There was a high the risk score value for the prediction in clinicopathological features. The forest plots showed that age, N stage and the RiskScore were the significant independent risk indicators. T cells CD4 memory resting and Mast cells are the amplest immune cell subpopulations in the high-score individuals. The expression of 5 CRGs exhibited significant differences in PC cell lines and tissues, LIPT1-knockdowning inhibited proliferation and invasion of pancreatic cancer cell lines. Conclusion Five CRGs relevant to pancreatic cancer prognosis were identified. Meanwhile, a new and accurate five CRGs prognostic model of pancreatic cancer was constructed. In addition, LIPT1 may promote proliferation, invasion and migration of pancreatic cancer cell lines. This may have a specific guiding value for future development of precise anti-cancer treatment strategies.